2018
DOI: 10.1038/s41598-018-29527-y
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils enhance early Trypanosoma brucei infection onset

Abstract: In this study, Trypanosoma brucei was naturally transmitted to mice through the bites of infected Glossina morsitans tsetse flies. Neutrophils were recruited rapidly to the bite site, whereas monocytes were attracted more gradually. Expression of inflammatory cytokines (il1b, il6), il10 and neutrophil chemokines (cxcl1, cxcl5) was transiently up-regulated at the site of parasite inoculation. Then, a second influx of neutrophils occurred that coincided with the previously described parasite retention and expans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 38 publications
4
43
0
Order By: Relevance
“…In contrast, neutrophils can play a role in the establishment and persistence of the parasite infection. A recent study revealed that the rapid recruitment of neutrophils to the dermal bite site of T b brucei infected tsetse flies, did contribute to higher systematic parasitemia levels during the onset of infection …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, neutrophils can play a role in the establishment and persistence of the parasite infection. A recent study revealed that the rapid recruitment of neutrophils to the dermal bite site of T b brucei infected tsetse flies, did contribute to higher systematic parasitemia levels during the onset of infection …”
Section: Discussionmentioning
confidence: 99%
“…Single-cell spleen suspensions were prepared at 0, 4,5,6,7,8,9,10,14,17,21,24 and 28 days post-infection (dpi) as previously described. 13 Unless otherwise stated, cell suspensions were re-suspended in 0.05% FBS BD FACSFlow Sheath Fluid.…”
Section: Cell Isolation and Flow Cytometry Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…One obvious cellular player than comes to mind when considering dermal immunology is the presence of neutrophils. Surprisingly, a recent study addressing the role of these innate cells during the onset of infection has shown that they have an infectionenhancing effect, rather than an inhibitory function (27). While the functional role of these cells has not been addressed in other immune sites, their cell number increases dramatically in the spleen of trypanosome infected mice (28).…”
Section: Trypanosome Growth and Reduce Parasite Fitness Is Controlledmentioning
confidence: 99%
“…While Plasmodium sporozoites reach the draining LN in the first hour after inoculation in the skin (Amino et al, 2006) African trypanosomes take longer as the first parasites are detected in LN 18 h after infection with tsetse flies (Caljon et al, 2016). IVM studies revealed that engulfment of trypanosomes by neutrophils at the inoculation site was rarely observed and was restricted to parasites with reduced motility/viability whereas live parasites escape phagocytosis (Caljon et al, 2018) (Fig. 2Cii IVM studies combined with flow cytometry showed that Leishmania mexicana use neutrophils as a safe transient shelter and that this impacts parasite-specific immune response in mice.…”
Section: Biological Findings In Parasitology: the Lymph Nodesmentioning
confidence: 99%